(untitled) (Journal of the Bangladesh Agricultural University, 2025)
Sweetmeats and fermented dairy items are important socioeconomic components of Bangladeshi culture. The study was aimed to assess the recent scenario of milk-based different sweetmeats traditional manufacturing techniques, practicing quality assurance, their distribution patterns and marketing in Bangladesh. A structured questionnaire was developed and utilized to collect data from local manufacturers of dairy products along with sweetmeat shopkeepers who consider the consumer’s demand based on their taste, health and affordability. Face-to-face interviews with 107 local sweetmeat processors were performed in 14 districts from five divisions in Bangladesh and analyzed those data. The findings revealed that dairy product manufacturing was the primary occupation and independent for the sweetmeat shopkeepers (86.67%), most having over 20 years of experience in making and selling the products. With few exceptions, the majority of sweetmeat shops had manufacturing space adjacent to their shops. Raw milk was mainly procured from vendors/middlemen/goala (50.47%) followed by directly from local dairy farmers (32.71%), the local market (11.21%), and lowest from their own farms (5.61%). For the production of different dairy sweets, cow milk (100%) was preferred. The products were categorized by 3 major groups namely fermented (mainly doi), wet sweets (different types of rasogolla) and dry sweets (sandesh, peda etc.) Fermented dairy products such as doi, along with various sweetmeats, were widely produced, with doi and rasogolla available in 100% of surveyed shops. Pricing varied based on region, with city areas exhibiting higher costs due to increased demand and production expenses. Quality assurance practices were common to all processors, primarily based on chhana yield (100%), with only 26.17% utilizing lactometers to assess the quality. Seasonal variations and special occasions significantly influenced production and sales. Moreover, the qualities of a dairy product were also assessed by hearing from consumer’s taste and affordability. The findings highlight both opportunities and constraints in Bangladesh’s sweetmeats and fermented dairy sector to facilitating market access and promoting their products locally and nationally. J Bangladesh Agril Univ 23(3): 431–441, 2025